High-throughput optimization of antibody production in CHO cells by tuning heavy- and light-chain promoter strength - Rahimi, Marzia; Adams, Anna Christina; Grav, Lise M.; Nielsen, Lars K.; Lavado-García, Jesús (Frontiers in Bioengineering and Biotechnology, 2026)
Monoclonal antibody (mAb) production in CHO cells depends, among other factors, on balanced co-expression of the heavy (HC) and light (LC) chains. Imbalances between HC and LC can reduce titer, compromise product quality, and negatively affect cell viability, which means that the optimal LC/HC expression ratio should be identified as early as possible in cell line development. However, systematically testing multiple LC/HC expression ratios for many antibody candidates using traditional workflows is slow and resource intensive. Here, we present a high-throughput screening platform, coupled with a design-of-experiments (DoE) strategy, to identify optimal LC/HC expression balance at the transient stage. The system uses single-vector constructs encoding both LC and HC under promoters of defined low, medium, or high strength, enabling combinatorial testing of LC/HC promoter pairs. We applied this workflow to three different antibodies and quantified titer, viable cell density, and viability 72 h post-transfection. The optimal LC/HC promoter ratio was antibody specific. For two antibodies, high LC combined with medium HC expression yielded the highest titer while maintaining cell viability. High LC with high HC expression (LC100–HC100) also produced high titer but caused reduced viable cell density and viability. For the third antibody, the best-performing configuration was medium LC with medium HC, with medium LC and high HC as a close second. Across all three antibodies, low-strength promoters for either chain consistently resulted in poor titer. Overall, this platform offers a rapid and scalable approach to define antibody-specific LC/HC promoter strength combinations that maximize productivity without compromising cell health, enabling more informed construct selection before committing to stable clone generation.